2003
DOI: 10.1038/sj.bjc.6601015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of transmembrane 4 superfamily in colon cancer

Abstract: Cell motility is an important cellular function closely related to the processes of tumour progression and metastasis. Several members of transmembrane 4 superfamily (TM4SF) have been reported to be associated with cell motility and metastatic potential of solid tumour. The aim of this study is to clarify the clinical significance of the member of TM4SF (MRP-1/CD9, KAI1/CD82 and CD151) in human colon cancer. We studied 146 colon cancer patients who underwent curative surgery and studied the expression of MRP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 31 publications
6
81
1
Order By: Relevance
“…Both domains are required for the anchoring of actin microfilaments at the cell membrane via a-actinin, a process regulated by the cytoplasmic tail of EpC (22). On the other hand, and in line with cell-cell adhesion preventing metastasis formation (23), EpC has been reported to abrogate E-cadherin -mediated cellcell adhesion by disrupting the link between a-catenin and F-actin (3,24), which points to a possible involvement of EpC in tumor progression (25). In addition, EpC can support cell motility and become involved in signal transduction and cell proliferation via up-regulation of cyclin A and cyclin E synthesis (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…Both domains are required for the anchoring of actin microfilaments at the cell membrane via a-actinin, a process regulated by the cytoplasmic tail of EpC (22). On the other hand, and in line with cell-cell adhesion preventing metastasis formation (23), EpC has been reported to abrogate E-cadherin -mediated cellcell adhesion by disrupting the link between a-catenin and F-actin (3,24), which points to a possible involvement of EpC in tumor progression (25). In addition, EpC can support cell motility and become involved in signal transduction and cell proliferation via up-regulation of cyclin A and cyclin E synthesis (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…CD9 transfection into Chinese hamster ovary, MHO10, ARH77, and MAC 10 cells, for example, inhibited cell motility (Ikeyama et al 1993, Miyake et al 2000. Many clinical studies have revealed that reduced CD9 expression is associated with a poor prognosis in various cancers, including non-small-cell lung cancers, breast cancers, and colon cancers (Huang et al 1998, Funakoshi et al 2003, Hashida et al 2003. Although originally identified as a surface antigen on a pre-B cell line (Kersey et al 1981), CD9 is also expressed on blastocysts in mice and endometrium epithelial cells in human and cattle (Le Naour et al 2000, Park et al 2000, Xiang & MacLaren 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroglobulin measurement in the elute from fine needle aspiration (Tg-FNA) is an emerging technique used to diagnose neck metastases and recurrence. Tg-FNA is not affected by the presence of serum Tg antibodies (2). This modality combined with cytology increases the sensitivity of detecting PTC metastases from 76% to 100% (3,4).…”
Section: Dilated Cardiomyopathy In a Patient With Cushing's Syndrome mentioning
confidence: 99%
“…The production of tumour necrosis factor (TNF) alpha and other Th1 cytokines by the placenta are associated with chorioamnionitis and preterm delivery [1]. It has been observed that TNF alpha levels are higher in placentas from normal deliveries compared to preterm and premature rupture of membrane deliveries [2]. We were interested in characterising the response to an inflammatory challenge in placentae collected from term and preterm deliveries and whether there were any differences in the inhibitory effect of glucocorticoids on this pathway with gestational age.…”
Section: Do Exosomes From Placental Explantsmentioning
confidence: 99%